The development, validation and testing of a vital signs monitoring tool for early identification of deterioration in adult surgical patients - Kyriacos, Una (Division of Nursing and Midwifery, 2015)
Patients often exhibit premonitory abnormalities in vital signs before an adverse clinical outcome. Patient survival may depend on the decisions of nurses to call for assistance. There is a paucity of published early warning scores (EWS) literature for general ward use from South Africa. In a public hospital in South Africa, the study aimed to develop, validate and test the impact of implementation of a modified early warning scoring (MEWS) system vital signs chart and training programme designed to improve hospital nurses’ performance in early identification of postoperative clinical and physiological deterioration in adult patients.